Deep Learning and Multiplex Networks for Accurate Modeling of Brain Age - Amoroso, Nicola; La Rocca, Marianna; Bellantuono, Loredana; Diacono, Domenico; Fanizzi, Annarita; Lella, Eufemia; Lombardi, Angela; Maggipinto, Tommaso; Monaco, Alfonso; Tangaro, Sabina; Bellotti, Roberto (Frontiers in Aging Neuroscience, 2019)
Recent works have extensively investigated the possibility to predict brain aging from T1-weighted MRI brain scans. The main purposes of these studies are the investigation of subject-specific aging mechanisms and the development of accurate models for age prediction. Deviations between predicted and chronological age are known to occur in several neurodegenerative diseases; as a consequence, reaching higher levels of age prediction accuracy is of paramount importance to develop diagnostic tools. In this work, we propose a novel complex network model for brain based on segmenting T1-weighted MRI scans in rectangular boxes, called patches, and measuring pairwise similarities using Pearson's correlation to define a subject-specific connectivity network. We fed a deep neural network with nodal metrics, evaluating both the intensity and the uniformity of connections, to predict subjects' ages. Our model reaches high accuracies which compare favorably with state-of-the-art approaches. We observe that the complex relationships involved in this brain description cannot be accurately modeled with standard machine learning approaches, such as Ridge and Lasso regression, Random Forest and Support Vector Machines, instead a deep neural network has to be used.